2014
DOI: 10.6026/97320630010419
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance of E. coli isolates from urine samples of Urinary Tract Infection (UTI) patients in Pakistan

Abstract: Drug resistance is becoming alarming with the passage of time worldwide in general and in third world countries in particular. Human urine specimens of patients of urinary tract infection at Sheikh Zayed hospital, Lahore, Pakistan were analyzed for drug resistance in Escherichia coli. A total of 69 Escherichia coli isolates from human urine specimens were obtained and screened for their antibiograms. A total of seven antibiotic resistance profiles were obtained with over 65% of the isolates showing multi-drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
4
11
0
1
Order By: Relevance
“…AMs, especially fluoroquinolones, are frequently prescribed in GIT infections (bacterial origin) to lessen the severity of infection and to minimize other symptoms [ 35 ]. Patients suffering from UTI are frequently prescribed with cephalosporins and penicillins [ 36 ]. Acute bronchitis is mostly caused by bacteria and viruses and AMs are prescribed to reduce the duration of cough and other symptoms [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMs, especially fluoroquinolones, are frequently prescribed in GIT infections (bacterial origin) to lessen the severity of infection and to minimize other symptoms [ 35 ]. Patients suffering from UTI are frequently prescribed with cephalosporins and penicillins [ 36 ]. Acute bronchitis is mostly caused by bacteria and viruses and AMs are prescribed to reduce the duration of cough and other symptoms [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rates of antibiotic resistance in our study were different from some studies in other countries. [ 18 34 35 36 37 ] MDR rate was higher in inpatients isolates (68%). A significant high resistance to SXT (61.2%) was found in the present study while many guidelines recommend this drug for UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…Imipenem resistance rate to E coli is 32.5% in a study of Pakistan. [35] Another study in Bangladesh has shown Meropnem resistance rate to E coli is 10.5%. [36] Antibiotics resistance depends on the genetic mutation and locality.…”
Section: Discussionmentioning
confidence: 99%